2005
DOI: 10.1111/j.1365-2362.2005.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer immunotherapy by fusions of dendritic and tumour cells and rh‐IL‐12

Abstract: Immunotherapy using a FC vaccine and rhIL-12 induced no serious adverse reactions, and provided good therapeutic responses in some of the patients with a brain tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
0
29
1
Order By: Relevance
“…However, immune response or immune memory against tumor antigens might have later arisen systemically because the disappearance or shrinkage in size of tumors was found at areas distant from the treated tumor, and no metastasis in any other organs was found. Other cytokines which have been used together with DCs in clinical treatment are IL-2 and IL-12 (32)(33)(34)(35). Like IFNγ, these cytokines also polarize immune responses to T helper type 1, but their effect on clinical response and immune responses against tumors was less clear than that of IFNγ found in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…However, immune response or immune memory against tumor antigens might have later arisen systemically because the disappearance or shrinkage in size of tumors was found at areas distant from the treated tumor, and no metastasis in any other organs was found. Other cytokines which have been used together with DCs in clinical treatment are IL-2 and IL-12 (32)(33)(34)(35). Like IFNγ, these cytokines also polarize immune responses to T helper type 1, but their effect on clinical response and immune responses against tumors was less clear than that of IFNγ found in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…We have reported that fusions of monocyte-derived immature DCs and autologous breast cancer, ovarian cancer, acute myeloid leukemia, or colorectal cancer cells induce antitumor immune responses against autologous tumor in vitro (10,(12)(13)(14)(15)(16). In phase I clinical trials in patients with melanoma, glioma, gastric, breast, and renal cancer, vaccination with DCs/tumor FCs was associated with immunologic and clinical responses (17)(18)(19)(20)(21)(22). Although the DCs/tumor fusion strategy has enormous potential in mice study, results from early clinical trails have been unsatisfactory (8 -11, 17-22).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…We have previously reported that immature (Imm) DCs (Imm-DCs) fused with autologous tumor cells can induce Ag-specific polyclonal CTLs in vitro (7)(8)(9)(10)(11). Although immunization with DC/tumor cell FCs in patients with cancer has been associated with immunological responses in phase I clinical trials, early clinical trials have shown only limited success (12)(13)(14)(15)(16)(17). Because this DC/tumor cell FC approach was developed in animal studies, many adjuvants, including IL-2, IL-12, IL-18, and synthetic oligodeoxynucleotides (ODNs) containing specific bacterial unmethylated CpG motifs (CpG ODNs), have been used to enhance the ability of DC/tumor cell FC vaccines to evoke antitumor immune responses (18 -22).…”
Section: Synergistic Induction Of Antigen-specific Ctl By Fusions Of mentioning
confidence: 99%